Early-age Performance of Cement Combination Concrete - Samuel Olufemi Folagbade (Civil Engineering Dimension, 2017)
Heat of hydration up to 72 hours and compressive strength up to 7 days of Portland cement and 17 binary and ternary cements containing fly ash, silica fume, and metakaolin, at a water/cement ratio of 0.50 and addition contents of 20%, 35%, and 55%, were used to examine the early-age performance of concrete. Results revealed that early-age performance depends on the fineness, heat of hydration, and dilution effect of cement combinations. Fly ash, due to dilution effect, reduces the heat of hydration and compressive strength. Using silica fume and metakaolin with increasing content of up to 10% as binary and ternary cement components, due to their fineness and increased heat of hydration, supports the strength development. Most of the cement combinations met the standard of strength requirements for ordinary early-age performance of concrete, while only half of it satisfied the standard for high early-age performance.